2015
DOI: 10.1007/s10620-015-3879-2
|View full text |Cite
|
Sign up to set email alerts
|

Transducin (Beta)-Like 1 X-Linked Receptor 1 Correlates with Clinical Prognosis and Epithelial–Mesenchymal Transition in Hepatocellular Carcinoma

Abstract: Our finding suggested that TBLR1 is likely to be a potential prognostic indicator and therapeutic target for HCC and that TBLR1 may be implicated in EMT of HCC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…Thus, it is critical to take measures to predict and reduce tumor recurrence. So far, previous studies have shown that tumor recurrence after surgical resection could be predicted by many tumor‐related factors, including tumor properties histological characteristics and inflammation‐related markers …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is critical to take measures to predict and reduce tumor recurrence. So far, previous studies have shown that tumor recurrence after surgical resection could be predicted by many tumor‐related factors, including tumor properties histological characteristics and inflammation‐related markers …”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, TBL1XR1 was reported to function as a tumor suppressor and inhibit tumor growth, perhaps through regulating androgen receptor (AR) signaling pathway (Daniels et al 2014. However, TBL1XR1 has been reported to be highly expressed in cervical cancer , breast cancer , nasopharyngeal carcinoma , hepatocellular carcinoma (Kuang et al 2016), digestive cancers (Liu et al 2016a;Zhou et al 2016;Liu et al 2017), and ovarian cancer . However, the significance of TBL1XR1 in predicting clinical outcomes of EOC patients has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…High expression of TBL1XR1 mRNA exists widely in thyroid, breast and other human tissues . It is reported that TBL1XR1 also contributes to carcinogesis and tumour progression in cervical cancer, gastric cancer and hepatocellular carcinoma . Deletion of TBL1XR1 reduced the proliferation, invasion and resistance to therapy .…”
Section: Introductionmentioning
confidence: 99%